Modern approaches to the use of mesenchymal stem cells in oncohematology - Prymakova, Evgeniya; Krivenko, Svetlana; Smolnikova, Viktorya; Nazarova, Ekaterina; Symanovich, Alla; Yurkina, Ekaterina; Dedyulya, Nataliya; Romanova, Iryna; Milanovich, Natalya (Journal of the Belarusian State University. Ecology, 2025)
In recent decades, views on etiology and pathogenesis of hemoblastosis have changed significantly. Unfavorable environmental factors (both physical and chemical) are becoming increasingly important etiologically. The strategy and tactics of treatment of oncohematological diseases are constantly being improved, and hematopoietic stem cell transplantation remains the «gold standard» in the treatment of this pathology. The main limitation of hematopoietic stem cell transplantation is the development of one of the most severe complications, the graft-versus-host disease. Cell therapy, in which mesenchymal stem cells play a leading role, is currently the second line of therapy for this condition after corticosteroids. It is necessary to optimize the approach to choosing a biomedical cell product based on mesenchymal stem cells in order to increase the effectiveness of cell therapy. The present study analyzes changes in the subpopulation composition of lymphocytes from recipients of allogeneic hematopoietic stem cells with signs of a graft-versus-host disease when they are co-cultured with mesenchymal stem cells obtained from different donors. It has been shown that cultures of mesenchymal stem cells obtained from different donors have different immunoregulatory potential. A method is proposed that makes it possible to select the most suitable biomedical cell product based on mesenchymal stem cells in terms of immunological characteristics for the clinical application of the graft-versus-host reaction. The analysis of the effectiveness of the proposed method was carried out using the results of immunophenotyping of lymphocytes from 12 recipients of allogeneic hematopoietic stem cells with clinical manifestations of GVHD treated at the State Institution «MSPC ST and H».
Keywords: graft-versus-host disease; mesenchymal stem cells; biomedical cell product; subpopulation composition of lymphocytes